2014
DOI: 10.1002/2013ja019377
|View full text |Cite
|
Sign up to set email alerts
|

Auroral electrojet indices in the Northern and Southern Hemispheres: A statistical comparison

Abstract: The auroral electrojet (AE) index is traditionally derived from about 12 ground magnetometer observatories located around the average northern auroral oval location. The AE index calculation has only been performed with Northern Hemisphere data, because similar coverage in the Southern Hemisphere does not exist. In this study, eight southern auroral ground magnetometers and their near conjugate Northern Hemisphere counterparts are used to calculate conjugate AE indices for 274 days covering all four seasons fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…Since the longitudinal variation is different in the SH, and since the conductivity is different, an AE index derived from SH magnetometer measurements would be different from the standard index, even if the magnetometers were at conjugate points to those in the North. This was indeed shown by Weygand et al (2014), who used SH magnetometers that were close to the conjugate points of the NH AE stations.…”
Section: Asymmetry In Ionospheric Currents and Magnetic Field Perturbsupporting
confidence: 53%
See 1 more Smart Citation
“…Since the longitudinal variation is different in the SH, and since the conductivity is different, an AE index derived from SH magnetometer measurements would be different from the standard index, even if the magnetometers were at conjugate points to those in the North. This was indeed shown by Weygand et al (2014), who used SH magnetometers that were close to the conjugate points of the NH AE stations.…”
Section: Asymmetry In Ionospheric Currents and Magnetic Field Perturbsupporting
confidence: 53%
“…A number of previous studies have also investigated hemispheric differences and similarities in ground magnetometer measurements (see review by Wescott (1966) and the work by e.g., Viljanen and Tanskanen (2013), Weygand et al (2014) and references therein). Most of these studies have looked at time series, showing largely similar perturbations in the two hemispheres, which indicates that changes in ionospheric convection, and consequently currents, most often occur simultaneously in the two hemispheres (Yeoman et al 1993).…”
Section: Asymmetry In Ionospheric Currents and Magnetic Field Perturbmentioning
confidence: 99%
“…The results of Maclennan et al (1991) clearly showed the antiphase UT variation in the southern hemisphere index that is seen in Figure 1 for . The results of Weygand (2014) show the same feature, but the amplitudes of the north-south differences are considerably smaller than found by Maclennan et al (1991). Note that both of these studies lacked stations at the key longitudes in the southern hemisphere: between Mawson (MAW) at 62.9E and W Antarctic Ice Sheet Divide (WSD) at 247.1E, the only available station is Macquarie Island (MCQ), south of New Zealand at 159.0E.…”
Section: -I Universal Time Variations In Different Geomagnetic Indicesmentioning
confidence: 67%
“…The difference between model error and mean error indicates that when mean coefficients for storm times are used error increases and model is more consistent for negative storms. This may be due to the fact that AE is computed using the observatories close to the Arctic circle in the northern hemisphere (Kamide and Rostoker, 2004) while an asymmetric behavior of the Auroral Electrojet is observed in the Antarctic region (Weygand et al, 2014) .…”
Section: Resultsmentioning
confidence: 99%
“…GEC is a complicated function of solar, annual, seasonal, daily and hourly variability of interplanetary space, magnetosphere, plasmasphere and ionosphere. In that sense, it is connected to Auroral Electrojet (AE) index, which is a measure of global electrojet activity in the auroral zone (Davis and Sugiura, 1966;Hajkowicz, 1998;Weygand et al, 2014). The AE index is derived from geomagnetic variations in the horizontal component of the geomagnetic field along the auroral zone in the northern hemisphere.…”
Section: Introductionmentioning
confidence: 99%